Substantial Improvement of High Temperature Strength of New-Generation Nano-Oxide-Strengthened Alloys by Addition of Metallic Yttrium - Svoboda, Jiří; Bořil, Petr; Holzer, Jakub; Luptáková, Natália; Jarý, Milan; Mašek, Bohuslav; Dymáček, Petr (Materials (Basel, Switzerland), 2022)
Oxide-dispersion-strengthened (ODS) Fe-Al-Y2O3-based alloys (denoted as FeAlOY) containing 5 vol. % of nano-oxides have a potential to become top oxidation and creep-resistant alloys for applications at temperatures of 1100-1300 °C. Oxide dispersoids cause nearly perfect strengthening of grains; thus, grain boundaries with limited cohesive strength become the weak link in FeAlOY in this temperature range. One of the possibilities for significantly improving the strength of FeAlOY is alloying with appropriate elements and increasing the cohesive strength of grain boundaries. Nearly 20 metallic elements have been tested with the aim to increase cohesive strength in the frame of preliminary tests. A positive influence is revealed for Al, Cr, and Y, whereby the influence of Y is enormous (addition of 1% of metallic Y increases strength by a factor of 2), as it is presented in this paper.
Keywords: alloying with metallic yttrium; powder hot consolidation by rolling; tensile strength at 1100 °C; mechanical alloying (MA); oxide dispersion strengthened (ODS) alloy